Cover Feature: Synthetic Cancer‐Targeting Innate Immune Stimulators Give Insights into Avidity Effects (ChemBioChem 5/2018). (16th February 2018) - Conibear, Anne C.; Pötgens, André J. G.; Thewes, Karine; Altdorf, Claudia; Hilzendeger, Clarissa; Becker, Christian F. W.
Abstract : The cover feature picture shows three men on a climbing wall representing molecules binding to a cell with one, two or four binding moieties. To explore avidity effects on immune stimulation and cancer cell binding, chemoselective ligations were used to assemble molecules that mimic the functions of antibodies with various numbers and combinations of immune‐stimulating and cancer‐targeting peptides. More information can be found in the full paper by A. C. Conibear, C. F. W. Becker et al. onpage 459 in Issue 5, 2018 (DOI:10.1002/cbic.201700522 ).